Magnetic Vestibular Stimulation in Subjects with Unilateral Labyrinthine Disorders - Bryan Kevin Ward; Dale C Roberts; Charles C Della Santina; Charles C Della Santina; John P Carey; David S Zee; David S Zee; David S Zee; David S Zee (Frontiers in Neurology, 2014)
We recently discovered that static magnetic fields from high-strength MRI machines induce nystagmus in all normal humans, and that a magnetohydrodynamic (MHD) Lorentz force, derived from ionic currents in the endolymph and pushing on the cupula, best explains this effect. Individuals with no labyrinthine function have no nystagmus. The influence of magnetic vestibular stimulation (MVS) in individuals with unilateral loss of labyrinthine function is unknown and may provide insight into mechanism of MVS. These individuals should experience MVS, but with differences consistent with their residual labyrinthine function. We recorded eye movements in the static magnetic field of a 7T MRI machine in nine individuals with unilateral labyrinthine hypofunction, as determined by head impulse testing and vestibular-evoked myogenic potentials (VEMP). Eye movements were recorded using infrared videooculography. Static head positions were varied in pitch with the body supine, and slow-phase eye velocity (SPV) was assessed. All subjects exhibited predominantly horizontal nystagmus after entering the magnet head-first, lying supine. The SPV direction reversed when entering feet-first. Pitching chin-to-chest caused subjects to reach a null point for horizontal SPV. Right unilateral vestibular hypofunction (UVH) subjects developed slow-phase-up nystagmus and left UVH subjects, slow-phase-down nystagmus. Vertical and torsional components were consistent with superior semicircular canal excitation or inhibition, respectively, of the intact ear. These findings provide compelling support for the hypothesis that MVS is a result of a Lorentz force and suggest that the function of individual structures within the labyrinth can be assessed with MVS. As a novel method of comfortable and sustained labyrinthine stimulation, MVS can provide new insights into vestibular physiology and pathophysiology.